Evolutionary diversification of insulin-related peptides (IRPs) in aphids and spatiotemporal distribution in Acyrthosiphon pisum. (February 2022) - Huygens, C.; Ribeiro Lopes, M.; Gaget, K.; Duport, G.; Peignier, S.; De Groef, S.; Parisot, N.; Calevro, F.; Callaerts, P.
Abstract: Members of the insulin superfamily activate the evolutionarily highly conserved insulin/insulin-like growth factor signaling pathway, involved in regulation of growth, energy homeostasis, and longevity. In the current study we focus on aphids to gain more insight into the evolution of the IRPs and how they may contribute to regulation of the insulin-signaling pathway. Using the latest annotation of the pea aphid ( Acyrthosiphon pisum) genome, and combining sequence alignments and phylogenetic analyses, we identified seven putative IRP encoding-genes, with IRP1-IRP4 resembling the classical insulin and insulin-like protein structures, and IRP5 and IRP6 bearing insulin-like growth factor (IGF) features. We also identified IRP11 as a new and structurally divergent IRP present in at least eight aphid genomes. Globally the ten aphid genomes analyzed in this work contain four to 15 IRPs, while only three IRPs were found in the genome of the grape phylloxera, a hemipteran insect representing an earlier evolutionary branch of the aphid group. Expression analyses revealed spatial and temporal variation in the expression patterns of the different A. pisum IRPs. IRP1 and IRP4 are expressed throughout all developmental stages and morphs in neuroendocrine cells of the brain, while IRP5 and IRP6 are expressed in the fat body. IRP2 is expressed in specific cells of the gut in aphids in non-crowded conditions and in the head of aphids under crowded conditions, IRP3 in salivary glands, and both IRP2 and IRP3 in the male morph. IRP11 expression is enriched in the carcass. This complex spatiotemporal expression pattern suggests functional diversification of the IRPs. Graphical abstract: Image 1 Highlights: The Acyrthosiphon pisum genome encodes seven insulin-related peptides (IRP), including the structurally divergent IRP11. IRP structures are evolutionarily conserved across aphid species. A. pisum IRPs show variations in spatial and temporal expression patterns.